The Cognitive Path to Inner Peace: Contemplation and Cognitive Regulation as a Path to Peace of Mind - Aisyah Jihan Hanifah; Moch Taufiq Ridho (Westscience Press, 2026)
Overthinking, anxiety, and mental restlessness stem from excessive thought patterns and the complex pressures of modern life are increasingly experienced by individuals in the contemporary era. Cognitive psychology holds that a person's emotional state is greatly influenced by the process of thought processing and interpretation of lived experience. From an Islamic perspective, the concept of tafakur emerges as a reflective activity involving deep mindful awareness of the self, life, and the greatness of Allah. This study aims to analyze the relationship between tafakur and cognitive regulation in cultivating inner peace through a library research approach, drawing on cognitive psychological theory and Islamic literature. The findings indicate that meditation functions as a form of cognitive regulation that assists individuals in reinterpreting negative thoughts, enhancing meaning in life, and building psychological tranquility. Thus, the integration of meditation and cognitive psychology can serve as an alternative approach to maintaining mental health and individual psychological well-being.